Steel, Administered Prices and Inflation: Comment - Macesich, George (Quarterly Journal of Economics, 1961)
Journal Article Steel, Administered Prices and Inflation: Comment Get access George Macesich George Macesich Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 3, August 1961, Pages 498–500, https://doi.org/10.2307/1885137 Published: 01 August 1961